Total, academic and artistic self-concepts of art school students and their associations with their art achievement - Wong, Xi Ying (2020)
Students' self-concept has been a predictor to academic achievements, but how this would work for the performing arts and visual arts majors is unknown. The thesis investigates the profile of self-concept of artistically and musically talented students, urged by the fact that gifted students, in general, were reported to have low self-concept and suffered from societal-behavioural problems. A total of 337 Form Three students was set as the operational population for data collection. A total of 232 samples were taken from Malaysian Art School or Sekolah Seni Malaysia located at several branches nationwide. Data was collected at art schools in an appropriate classroom over one week with students completing all three instruments as groups. Self-concepts were collected using Self Description Questionnaire-II (SDQ II) and Arts Self Perception Inventory (ASPI). Simultaneously, the results of students' Form Three Evaluation or Pentaksiran Tingkatan 3 (PT3) were taken as an evaluation of achievement. It took approximately 30 minutes for the administration of the study. The profile created comprises information of total self-concept, academic self-concept, artistic self-concept and their associations with genders, artistic domains, and their art achievements. Artistically talented students have a moderately high level of self-concept, and their self-concept was significantly different between gender and the specific artistic domain. There is also a positive association between total self-concept and academic self-concept with art school students' art achievement. In understanding Malaysian Art School students, total self-concept and domain-specific self-concept are indicators for gender and domain differences. However, academic self-concept does not seem to be of much significance in revealing these students' characteristics. Meanwhile, domain-specific self-concept is not a predictor of art achievement, but total self-concept is when cross-domain artistry is concerned with Malaysia Arts School.